TEXT RECEPTION OF THE MANUSCRIPT SYARAH MA’RIFAT ISLAM WRITTEN BY SYEIKH IMAM ZAHID - Supriatna, Agus (International Review of Humanities Studies, 2023)
This article aims to explain the reception of the ancient text "Sharah Ma'rifat Islam" by Sheikh Imam Zahid. The method used in this research is a descriptive-analytic method with a philological approach and reception theory. This ancient manuscript of Syarah Ma'rifat Islam (SMI) contains lessons about Islamic Aqeedah. The results showed that SMI contained knowledge about the meaning of Islam, Iman, Ihsan, and issues related to believers, families, groups, ummah, and schools of thought. Nusantara scholars widely absorbed the SMI text to teach basic Aqidah lessons to their students. The SMI text is explained in more detail, such as in terms of language and content in the form of reference sources and the intent of each discussion section of the manuscript.